On random measures on spaces of trajectories and strong and weak solutions of stochastic equations - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate stationary random measures on spaces of sequences or functions. A new definition of a strong solution of a stochastic equation is proposed. We prove that the existence of a weak solution in the ordinary sense is equivalent to the existence of a strong measure-valued solution.